The Influence of Social Media on Understanding Islam Among Gen Z - Muhmmad Permadi; Atin Risnawati (Sekolah Tinggi Agama Islam Kuningan, 2026)
Backround: Generation Z, born and raised in the digital era, maintains a strong connection with technology particularly social media—as a primary source of information, including in the domain of Islamic understanding. Objective: This article examines how social media influences the Islamic understanding of Generation Z, encompassing both its benefits and challenges. Social media provides rapid and accessible pathways to diverse Islamic resources, offering interactive platforms such as digital lectures, online discussions, and supportive virtual communities that facilitate religious identity exploration. Method: This study employs a qualitative method with a case study approach to analyze the influence of social media on the Islamic understanding of Generation Z. Findings and Implications: The findings indicate that social media provides a broad range of resources that aid in religious education, including digital lectures and interactive online communities. However, challenges such as misinformation, distorted teachings, and short-form content that lacks depth are prevalent. These factors contribute to a fragmented understanding of Islam among Generation Z. The study also highlights the need for strategic approaches to foster digital literacy and collaborate with scholars and content creators to ensure that Islamic content is accurate and contextually grounded. Conclusion: While social media has the potential to enhance Islamic understanding among Generation Z, it also poses risks related to the spread of misinformation and radical ideologies. To address these issues, it is crucial to cultivate digital literacy, ensure the production of credible Islamic content, and encourage collaboration between scholars and digital platforms.